2016
DOI: 10.3389/fpls.2016.01112
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of ROS Accumulation in the Stigmas of Angiosperms and Visions into Their Multi-Functionality in Plant Reproduction

Abstract: Accumulation of reactive oxygen species (ROS) in the stigma of several plant species has been investigated. Four developmental stages (unopened flower buds, recently opened flowers, dehiscent anthers, and flowers after fertilization) were analyzed by confocal laser scanning microscopy using the ROS-specific probe DCFH2-DA. In all plants scrutinized, the presence of ROS in the stigmas was detected at higher levels during those developmental phases considered “receptive” to pollen interaction. In addition, these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
26
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 31 publications
7
26
2
Order By: Relevance
“…As expected, a gradual increase in H 2 DCF-DA fluorescence was observed from stage S1 to S5 stigmas, indicating the high-level ROS accumulation in mature stigmatic papillae close to flower opening (Supplemental Figure 3). This is consistent with previous reports on ROS accumulation in mature stigmas of angiosperms (Zafra et al, 2016). It is worth noting that this increase in ROS coincided with a dramatic reduction in proteins involved in flavonoid biosynthesis.…”
supporting
confidence: 93%
“…As expected, a gradual increase in H 2 DCF-DA fluorescence was observed from stage S1 to S5 stigmas, indicating the high-level ROS accumulation in mature stigmatic papillae close to flower opening (Supplemental Figure 3). This is consistent with previous reports on ROS accumulation in mature stigmas of angiosperms (Zafra et al, 2016). It is worth noting that this increase in ROS coincided with a dramatic reduction in proteins involved in flavonoid biosynthesis.…”
supporting
confidence: 93%
“…The stigma exudate had been traditionally regarded as a reservoir of water, secondary metabolites, cell wall precursors and compounds that serve as energy supply for rapid pollen tube growth (Konar & Linskens 1966;Labarca et al 1970), but recent studies revealed some active compounds, at least in several species (Rejón et al 2014) that modulate pollen germination, such as calcium (Ge et al 2009) and enzymes of catabolism and defense (Rejón et al 2013). We found ROS in collected stigma exudate of tobacco, which agrees well with the previously reported fact of ROS synthesis and accumulation on stigmas of different species (McInnis et al 2006a;Zafra et al 2016), including sunflower (Sharma & Bhatla 2013), olive (Zafra et al 2010), Senecio squalidus L. and Arabidopsis thaliana (McInnis et al 2006b). ROS signaling in pollen germination has been assumed and discussed (Wudick & Feijo 2014) and putative mechanisms of ROS action on male gametophyte have been revealed in vitro (Wu et al 2010;Breygina et al 2016;Podolyan et al 2019).…”
Section: Discussionsupporting
confidence: 90%
“…The decreased ROS levels in the ornamental kale stigma after treatment with exogenous flavonoid (kaempferol) do not compromise the SI response of the stigma, but the attachment and germination of the compatible pollen is drastically reduced. In contrast, the adherence of pollen grains that trigger the decrease of ROS in the stigma and nitric oxide (NO) from the adhesive pollen as the inducing factor for ROS decrease have been suggested (Hiscock et al, 2007;Serrano et al, 2011;Sharma and Bhatla, 2013), which further supports the suggestion that regulation of the ROS in the stigma is involved in the signaling for pollen-stigma interactions (Hiscock and Allen, 2008;Zafra et al, 2016). Therefore, a possible scenario is that the levels of higher ROS in the mature stigma are favorable for the early stage of the pollen-stigma interaction, e.g., pollen adhesion and hydration, and the decrease in the ROS in the stigma after pollen landing might provide a surrounding for compatible pollen tube growth in the stigma tissue ( Figure 1A).…”
Section: Ros Involved In Pollen Hydration and Germination On The Stigmamentioning
confidence: 81%
“…The compromised adhesion and germination of the pollen grains on the non-stigma surfaces indicate that the stigma factors are important for the pollen-stigma interaction (Ma et al, 2012). ROS accumulation is found in the stigmas of various angiosperm species, including Magnolia (a primitive angiosperm) and Arabidopsis (McInnis et al, 2006;Zafra et al, 2016). Stigma receptivity is correlated with the activity of ROS-related enzymes, such as superoxide dismutase and peroxidase (McInnis et al, 2005;Sharma and Bhatla, 2013), indicating that ROS accumulation in the stigma is a self-regulated process.…”
Section: Ros Involved In Pollen Hydration and Germination On The Stigmamentioning
confidence: 99%